2016
DOI: 10.1007/s12187-016-9385-z
|View full text |Cite
|
Sign up to set email alerts
|

Body Image, Self-Esteem, and Depression in Korean Adolescents

Abstract: This study examined the association among body image, self-esteem, and body image and depression in a sample of 3658 Korean adolescents (male 53.4 %). The extant research on these relationships have been conducted primarily on samples from Western countries, where although thinness is similarly pursued findings have limited generalizability due to differences in societal context. Participants from South Korea completed assessment measures of body image, self-esteem, and depression. Hierarchical regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
(35 reference statements)
2
8
0
1
Order By: Relevance
“…This study found that self-esteem had a significant positive effect on sports participation; a higher self-esteem led to a tendency to engage in and be attached to sports, and a lower self-esteem resulted in denial and alienation of sports. This result was nearly consistent with the findings of Korkmaz (2014) and You et al (2017), and it has also proven Birkimer et al (1996) findings that that self-esteem was helpful in promoting the sports participation, and self-esteem was also one of the motivations to drive sports participation. In addition, the study also found that body image had a significant positive effect on self-esteem; the more positive the body image, the higher the level of self-esteem, which was consistent with Guo et al (2017) study.…”
Section: Relationship Of Personal Background With Self-efficacy Selfsupporting
confidence: 89%
“…This study found that self-esteem had a significant positive effect on sports participation; a higher self-esteem led to a tendency to engage in and be attached to sports, and a lower self-esteem resulted in denial and alienation of sports. This result was nearly consistent with the findings of Korkmaz (2014) and You et al (2017), and it has also proven Birkimer et al (1996) findings that that self-esteem was helpful in promoting the sports participation, and self-esteem was also one of the motivations to drive sports participation. In addition, the study also found that body image had a significant positive effect on self-esteem; the more positive the body image, the higher the level of self-esteem, which was consistent with Guo et al (2017) study.…”
Section: Relationship Of Personal Background With Self-efficacy Selfsupporting
confidence: 89%
“…More than one third of adolescent mothers were employed, while more than three fifths were house-wives. This is similar to study conducted by [20] in Korea, who found that the largest portion (42.8 %) of the sample reported their father's educational level were bachelor's degrees, followed by high school diplomas (40.3 %), post-bachelor's degrees (8.1 %), and middle school diplomas (3.5 %). Mothers were slightly less educated as it is mother's educational level were high school diplomas (50.5 %), bachelor's degrees (36.4 %), post-bachelor's degrees (4.0 %), and middle school diplomas (3.9 %).…”
Section: Discussionsupporting
confidence: 88%
“…A previous study comparing US and Korean middle school students found that Korean girls reported greater body dissatisfaction than US girls [6][7][8]. Additionally, Korean youths with a low level of body dissatisfaction were likely to exhibit a low level of self-esteem and a high level of depressive symptoms [2,9,10]. Consequently, research has been conducted to identify the causes of body dissatisfaction leading to adolescents' mental problems, to develop diverse intervention strategies (e.g., exercises and cognitive behavior strategy programs), and to test the effects of such strategies.…”
Section: Introductionmentioning
confidence: 99%